Oldest 'earthquake' in South Africa (Robben Island, 07 April 1620) discredited - Sharad Master (South African Journal of Science)
The oldest recorded earthquake in South Africa is widely accepted (in several seismic catalogues) to have occurred on 07 April 1620. This earthquake was regarded as having a Modified Mercalli Scale intensity of II-IV, corresponding to a Richter Scale Magnitude of ~4. An examination of the original sources on which the record of this earthquake rests, reveals that it was based on a description of 'two startling thunderclaps like cannon shots while ship was becalmed near Robben Island' by Augustin de Beaulieu, who was the head of a fleet of three ships which put in Table Bay in March-April 1620. A full excerpt of Beaulieu's account reveals that the thunderclaps took place in a short period of calm during an extended period of stormy weather, and that the observations were made on board ship, so that no seismic ground vibration was felt. The Western Cape has a much lower incidence of lightning than the interior of South Africa, and the fact that the thunderclaps were not accompanied by lightning is not unusual. Thus the simplest explanation of the thunderclaps is that they were the result of atmospheric phenomena, and not a result of seismic activity, as interpreted by J.N. Theron in 1974. The events of 07 April 1620 should thus be removed from the catalogues of historical seismicity in South Africa, making the slight shock felt in Cape Town in 1690, with a Modified Mercalli Scale intensity of III, the oldest recorded seismic tremor in the history of South Africa.